Asymmetric Information, Managerial Opportunism, Financing, and Payout Policies - NOE, THOMAS H.; REBELLO, MICHAEL J. (Journal of Finance, 1996)
ABSTRACT We examine corporate issuance and payout policies in the presence of both adverse selection (in capital markets) and managerial opportunism. Our results establish the importance of the locus of decision control in the firm. When shareholders determine policies, debt financing is always optimal in the presence of either adverse selection or managerial opportunism. However, when both of these problems are simultaneously present, equity issuance can become an optimal signaling mechanism. Shareholders' most preferred signaling mechanism is restricting dividends, followed by equity financing, and finally underpricing securities. When managers determine policies, a reversed hierarchy may be obtained.